Analisis Keterlaksanaan Materi Asam Basa Dalam Pembelajaran Kimia Di Kelas XI SMAN 1 Lembar - Rizka Sofia Irawan; Nisa Hidayatullah (FKIP University of Mataram, 2026)
This study aims to analyze the implementation of acid-base material in chemistry learning for grade XI students at SMAN 1 Lembar. The background of this study is the importance of acid-base chemistry, which has broad applications in everyday life, but students often have difficulty understanding the concept in depth. The research used a descriptive quantitative approach with purposive sampling, involving 3 chemistry teachers and 30 students who had studied the material. Data were collected through teacher and student questionnaires and learning observation sheets, and then analyzed as percentages to determine the implementation category. The results showed that the learning implementation was in the good category (61–75%). The learning evaluation indicator obtained the highest score (68%), while conceptual understanding received the lowest (61.07%). Learning planning (70.66%) was higher than implementation (64%), indicating a gap in curriculum implementation. The low conceptual understanding requires contextual and HOTS-based strategies, a wider variety of learning resources, the development of assessments that measure higher-order thinking skills, as well as support from school policies and ongoing teacher training.